Pemahaman dan Penanggulangan Bulllying di Tingkat Organisasi - Binsar Martua Valentino Sinaga; Mujahid Widian Saragih (JOURNAL SAINS STUDENT RESEARCH, 2024)
Bullying, which comes from English with the root word "bully", refers to the act of bullying or disturbing. In the context of psychology, bullying is defined as repeated negative behavior aimed at causing discomfort or suffering to someone who is unable to resist it. Some definitions describe bullying as aggressive behavior that is characterized by being destructive, repeated over a period of time, and involving an imbalance of power. Bullying is no longer limited to the school environment, but also extends to the workplace. This phenomenon causes serious problems, including intimidation, psychological pressure, discrimination, unfair treatment, verbal and non-verbal harassment, and cyberbullying. In an organizational context, bullying not only involves individuals but also has broad impacts, including reducing employee psychological well-being and decreasing productivity. Joint efforts from management and employees are needed to overcome the problem of bullying in the workplace. This includes intensive education on the concept of bullying, implementation of clear policies, and promotion of an inclusive work culture. By better understanding the negative impacts of bullying, it is hoped that awareness and response to this problem can be increased, creating a healthy and productive work environment for all members of the organization.